(untitled) (Praxis Educativa, 2023)
In this text we will address a series of reflections that explore the conceptions of body, corporeality and itself; trying to come up with a position on the subject. This work is nota contribution to phenomenology, nor is it even strictly indebted to it;;_ lt merely constitutes an incoherent/insurgent/chaotic/irreverent attempt to express a singular and subjective position that has ramifications in spaces apparently far from the academic field and distant from each other, such as the low rate of completion of theses and dissertations in postgraduate courses, the active resistance to death by dualism in the academic world, teacher training, the ethical dimension of evaluation and life itself.